Design of a Feedback Control System for Keda Torus Experiment Equilibrium Field Power Supply. (18th August 2017) - Bai, Wei; Lan, Tao; Yang, Lei; Xiao, Chijin; Li, Hong; Mao, Wenzhe; You, Wei; Xu, Hangqi; Deng, Tijian; Zhu, Junfeng; Luo, Bing; Fu, Peng; et al.
Abstract: An equilibrium field (EQ) power supply (PS) circuit using a feedback H-bridge pulse-width-modulation controller has been developed to control the plasma horizontal position and to satisfy the requirement of plasma equilibrium in the Keda Torus eXperiment (KTX) reversed field pinch. Results from simulations of plasma discharge aimed at achieving plasma equilibrium demonstrate the success of the PS circuit design. Additionally, this design provides a feasible control solution for achieving equilibrium conditions in future KTX PS upgrades. The details of the EQ model and simulations of the poloidal field circuit are presented and discussed in this technical note.